2-heteroaryl-[1,2,4]triazolo[1,5-c]quinazoline-5(6 H)-thiones and their S-substituted derivatives: Synthesis, spectroscopic data, and biological activity - Bilyi, A. K.; Antypenko, L. M.; Ivchuk, V. V.; Kamyshnyi, O. M.; Polishchuk, N. M.; Kovalenko, S. I.; Поліщук, Наталія Миколаївна; Коваленко, Сергій Іванович (My University, 2015)
In the continuing search for novel, biologically effective heterocyclic agents, several methods for the synthesis of 2-heteroaryl-[1,2,4]triazolo[1,5-c]quinazoline-5(6H)-thiones have been developed: thiolation of oxo derivatives, [5+1] cyclocondensation of [2-(3-heteroaryl-[1,2,4]triazol-5-yl)phenyl]amines with carbon disulfide, potassium ethyl xanthogenate, or aryl isothiocyanates, and in situ reaction of 2-isothiocyanatobenzonitrile with hydrazides. A series of N-R-2-[(2-heteroaryl-[1,2,4]triazole-[1,5- c]quinazoline-5-yl)thio]acetamides were obtained by aminolysis of the corresponding acetic acids and alkylation of potassium thiolates with N-R-2-chloroacetamides. It was established that some potassium thiolates, 4 a–4 d, 4 h, and 4i, had high antibacterial activity against Staphylococcus aureus with a minimum inhibitory concentration of 12.5 mgmL1 and minimum bactericidal concentration of 25 mgmL1 , which exceeded the values for trimethoprim. In addition, {2-[3-(1H-indole-2-yl)-1H-1,2,4-triazol-5-yl]phenyl}amine 2i was investigated in the concentration range 100–0.01 mm at 59 lines of nine cancer cell types, and showed a mean effective concentration at 3.12–7.03 mm and cytotoxic effect at 15.56–67.38 mm. The possible mechanisms of activity were predicted by molecular docking studies to S. aureus dihydrofolate reductase and epidermal growth factor receptor kinase.